CRISPR-Cas System in Antibiotic Resistance Plasmids in Klebsiella pneumoniae - Kamruzzaman, Muhammad; Iredell, Jonathan R. (Frontiers in Microbiology, 2020)
CRISPR-Cas (clustered regularly interspersed short palindromic repeats-CRISPR-associated protein) is a microbial adaptive immune system involved in defence against different types of mobile genetic elements. CRISPR-Cas systems are usually found in bacterial and archaeal chromosomes but have also been reported in bacteriophage genomes and in a few mega-plasmids. Klebsiella pneumoniae is an important member of the Enterobacteriaceae with which they share a huge pool of antibiotic resistance genes, mostly via plasmids. CRISPR-Cas systems have been identified in K. pneumoniae chromosomes, but relatively little is known of CRISPR-Cas in the plasmids resident in this species. In this study, we searched for CRISPR-Cas system in 699 complete plasmid sequences (>50-kb) and 217 complete chromosomal sequences of K. pneumoniae from GenBank and analysed the CRISPR-Cas systems and CRISPR spacers found in plasmids and chromosomes. We found 44 plasmids from Klebsiella species and 3 from other Enterobacteriaceae to carry a putative type IV CRISPR-Cas system with spacers targeting different plasmid and chromosome sequences. 45 of 47 plasmids with putative type IV CRISPR had IncFIB replicon and 36 of them had an additional IncHI1B replicon. All plasmids except one are very large (>200 kb) and half of them carried multiple antibiotic resistance genes including blaCTX-M, blaNDM, blaOXA. To our knowledge, this is the first report of multi drug resistance plasmids from Enterobacteriaceae with their own CRISPR-Cas system and it is possible that the plasmid type IV CRISPR may depend on the chromosomal Type I-E CRISPRs for their competence. Both chromosomal and plasmid CRISPRs target a large variety of plasmids from this species, further suggesting key roles in the epidemiology of large plasmids.